1998
DOI: 10.1046/j.1365-3040.1998.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and conductance of spring‐wheat leaves: field response to continuous free‐air atmospheric CO2 enrichment

Abstract: Spring wheat was grown from emergence to grain maturity in two partial pressures of CO 2 (pCO 2 ): ambient air of nominally 37 Pa and air enriched with CO 2 to 55 Pa using a free-air CO 2 enrichment (FACE) apparatus. This experiment was the first of its kind to be conducted within a cereal field without the modifications or disturbance of microclimate and rooting environment that accompanied previous studies. It provided a unique opportunity to examine the hypothesis that continuous exposure of wheat to elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
3
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 35 publications
9
64
3
1
Order By: Relevance
“…However, this is strongly species-specific; in loblolly pine (Pinus taeda L.) saplings fed nitrate as their sole N source, CO2 enrichment led to a suppression of growth compared to plants fed ammonium, while in the same study, neither elevated CO2 levels nor nitrogen form had much of an effect on wheat (Triticum aestivum L.) growth [24]. While some studies have demonstrated acclimatory decreases in leaf photosynthesis as a result of elevated CO2 levels [25], others have noted increases in leaf photosynthetic rates [26], which may be linked to decreased stomatal conductance and improved water use efficiency. Clearly there remain significant questions about the photosynthetic and growth responses in C3 grasses, and the importance of elevated CO2 to future productivity.…”
Section: Carbon Fixationmentioning
confidence: 91%
“…However, this is strongly species-specific; in loblolly pine (Pinus taeda L.) saplings fed nitrate as their sole N source, CO2 enrichment led to a suppression of growth compared to plants fed ammonium, while in the same study, neither elevated CO2 levels nor nitrogen form had much of an effect on wheat (Triticum aestivum L.) growth [24]. While some studies have demonstrated acclimatory decreases in leaf photosynthesis as a result of elevated CO2 levels [25], others have noted increases in leaf photosynthetic rates [26], which may be linked to decreased stomatal conductance and improved water use efficiency. Clearly there remain significant questions about the photosynthetic and growth responses in C3 grasses, and the importance of elevated CO2 to future productivity.…”
Section: Carbon Fixationmentioning
confidence: 91%
“…The magnitude of the stomatal response generally does not diminish with time in long-term experiments (Lee et al, 2001;Gunderson et al, 2002;Ainsworth et al, 2003). However, it does vary on hourly and daily timescales (Garcia et al, 1998;Rogers et al, 2004). On four dates during 2003, the varying effect of elevated [CO 2 ] on g s in soybean fumigated by FACE technology in the field could be predicted with the Ball et al (1987) model (Leakey et al, 2006a).…”
Section: Effects Of Elevated [Co 2 ] On Stomatal Conductancementioning
confidence: 98%
“…The use of open-top chambers provides unlimited rooting volume under field conditions. However, these chambers disrupt the coupling between the canopy and atmosphere, reduce exposure to wind, and alter precipitation and light environments of the canopy, thereby causing an effect of similar magnitude to, or even greater than, the CO 2 treatment itself (Allen et al 1992;Garcia et al 1998). The use of free air [CO 2 ] enrichment (FACE) technology ensures that plant growth and development occur in an environment that minimizes the potentially confounding effects of enclosures (Hendrey et al 1993;Kimball et al 1997;Garcia et al 1998;McLeod and Long 1999).…”
Section: Introductionmentioning
confidence: 99%